Support for Educational Technologies in the Interview for Child Organ and Tissue Donation - da Silva Knihs, Neide; Burg, Maria Carolina Candido; Silva, Ariadne Matzembacher da; Silveira, Emanuella Lima; Betta, Evelin da Silva Della; Treviso, Patricia; Costa, Juliana Martins; Silva, Luiza Anselmo Gonçalves da (Brazilian Journal of Transplantation, 2026)
Objectives: To identify available information to support the development of educational technologies in the context of family interviews for organ and tissue donation with parents of children and adolescents. Methods: This is an integrative literature review conducted in six stages, according to the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses: 1) elaboration of the research question; 2) search for primary studies in the literature; 3) extraction of data from the selected studies; 4) evaluation of the included studies; 5) analysis and synthesis of the results; 6) presentation of the review. The search for primary studies was conducted in the following databases: LILACS, PubMed, CINAHL, Embase, Scopus, SciELO, and Web of Science. The methodological quality was assessed according to the tool proposed by the Johns Hopkins Evidence-Based Practice Model for Nursing and Healthcare Professionals. Results: Twenty-one studies were included, with different designs, such as qualitative, cross-sectional, prospective, quasi-experimental, and mixed-methods studies. Among the strategies identified to support the development of educational technologies, the following stood out: training for communicating brain death, emotional support for families, management of religious and cultural beliefs, strengthening the bond with parents, and inclusion of the topic in academic training and continuing education. Conclusion: The evidence gathered reinforces the importance of a scientific basis in the development of effective educational technologies to qualify the performance of professionals in family interviews for organ and tissue donation of children and adolescents. The strategies identified show promise to guide future initiatives for training and development of educational technologies. However, the scarcity of studies with robust methodological designs highlights the urgent need for additional research to deepen the understanding of the topic and validate the application of these technologies in clinical practice.